Letramentos digitais: uma investigação acerca da avaliação na rede estadual de ensino do Ceará - Guedes, Lilian Kelly Alves (2024)
This work investigates the digital literacy practices based on what is planned by the Brazilian National Common Curricular Base (BNCC) and by the studies on literacy through the application of an evaluation that takes place in printed and digital formats. To do so, this research was based on three steps: the first one was to find out if and in what way, the skills in the BNCC for secondary education are covered in the matrix that guides the preparation of the test applied online in state schools in Ceará. This step was based on the studies by Street (2013, 1984), Kleiman (1995), Cosson (2015) and Dudeney, Hockly and Pegrum (2016). On the second step, Dias and Novais (2009) are brought into discussion in order to help to understand what skills were required from the students to be able to use and remain in the digital environment when taking the online test. Based on the work by Bakhtin (2003, 2006 and 2001) and Bakhtin and Voloshinov (1926), the content of the Portuguese language tests were analyzed in order to understand which is the relationship between digital literacy and the performed tests. The results show that the BNCC presents closer relations to the digital literacies, while the Matrix of Knowledge has few skills clearly related to them. The online environment only requires basic knowledge in order to be used by the students. Regarding the Portuguese Language test, it is clear that it still prioritizes more traditional reading procedures, despite the fact that this test also takes place in a digital environment. However, it is possible to explore reading through texts that are disseminated in digital environments.